An Ethnomathematic Exploration of Local Wisdom of Patrol Music in Jember Regency - Anjung, Rosdiana Suswati; Lutfiyah, Lutfiyah; Sulisawati, Dwi Noviani (International Journal of Trends in Mathematics Education Research, 2025)
This study aims to describe the form of ethnomathematics contained in patrol music as one of the local cultural heritages of the Jember Regency community. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews and documentation of local cultural actors. Based on the results of data collection, several traditional Jember musical instruments were obtained, namely kentongan, tambourine and flute. Based on the results of the exploration, it was found that there are mathematical concepts contained in the kentongan, tambourine, and flute musical instruments including size and measurement, spatial shapes, rhythmic patterns, rhythm and time, symmetry. Kentongan and tambourine are rhythmic musical instruments that use the concept of counting and patterns to create rhythm and beats. Meanwhile, the flute utilizes the concept of frequency and wavelength to produce different tones, which are also related to mathematics.